Microleakage Comparison among Three Orthodontic Brackets and Two Orthodontic adhesives - Mokhtar M. Al- Hamidi (Al-Rafidain Dental Journal, 2014)
AIMS:To evaluate and compare the microleakage occlusally and gingivally under bracket-composite interface of sapphire ceramic, stainless steel and composite orthodontic brackets bonded with two different generations of orthodontic adhesives.MATERIALS AND METHODS: Seventy-two freshly extracted premolars were utilized in this study. Three types of orthodontic brackets were used as follows: sapphire ceramic, composite and stainless steel. The samples were divided into two main groups of 36 samples; one group was bonded with Resilience® adhesive, while the other was bonded with Biofix adhesive. Each group was further subdivided into three subgroups of 12 samples according to bracket types. After photopolymerization, the samples were thermocycled. Samples were sealed with nail varnish, stained with 2% methylene blue dye then sectioned occlusogingivally, examined under a stereomicroscope and measured for microleakage at the bracket-adhesive interface from both occlusal and gingival margins, evaluated statistically with t- tests at p≤0.05 levels of significance. RESULTS: All groups showed various degrees of microleakage, however, no significant differences either between the two adhesives or among the three bracket types were recorded. Microleakage beneath sapphire brackets was significantly higher under the Biofix adhesive at the gingival side.CONCLUSION: No significant differences were recorded between the occlusal and gingival sites in all of the study groups.However, the 5th generation adhesive showed higher microleakage with significant difference under sapphire ceramic brackets at the gingival margin.